Lichen simplex chronicus on the scalp: exuberant clinical, dermoscopic, and histopathological findings - Bianca Pinheiro Bousquet Muylaert; Mayara Trindade Borges; Alexandre Ozores Michalany; Camila Raposo Cabral Scuotto (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Lichen simplex chronicus is a skin disease that mostly affects female patients, with a peak incidence between ages 35 and 50 years. On the scalp, it appears as a single or multiple oval lesions, showing scaling and hair shaft loss or breakage. An important dermoscopic feature of the disease are the "broom fibers." Histopathology reveals the "hamburger" and the "gear wheel" signs. The aim of this report is to demonstrate a case of lichen simplex chronicus on the scalp with typical and exuberant clinical, dermoscopic, and histopathological findings.